Modeling Islamic Economics and Finance Research: A Bibliometric Analysis - Rusydiana, Aam; Sanrego, Yulizar; Rahayu, Solihah (International Journal of Islamic Economics and Finance (IJIEF), 2021)
This study aims to determine the development map of mathematic model in islamic economics and finance research that is indexed by Scopus and other reputable journal with the keyword "Mathematic model in islamic economics and finance". The data analyzed were 100 selected publications. The development map of mathematic model in islamic economics and finance research analyzed using the VOSviewer application program to find out the bibliometric map. The results showed that the number of publications on the development of mathematic model in islamic economics and finance research indexed Scopus from 1983-2019 experienced a significant increase and the most were published in Journal of King Abdulaziz University: Islamic Economics. Network visualization showed that the map of the development of mathematic model in islamic economics and finance research was divided into 3 clusters. The majority of research is related to modeling of Profit Loss Sharing (PLS) schemes. However, despite the development of using mathematical model in those researches, the approach tends to be adaptive (inductive) from conventional models that already exist. A challenge to review the mainstream model need to be further critically reviewed. Hence, it is necessary for researcher to formulate a mathematical model with a deductive approach that is reduced from Islamic norms or ethics derived from the Alquran and Sunnah.